Untersuchung der Apoptose in kardialen und kardiovaskulären Erkrankungen : Bedeutung von Stickstoffmonoxid - Weiland, Ulrike; Justus Liebig University Giessen (My University, 1999)
Die Bedeutung der Apoptose und die zugrundeliegenden Mechanismen in verschiedenen pathophysiologischen Zuständen des Herzens sind noch weitgehendungeklärt und es bleibt zu zeigen, daß die Apoptose-Signaltransduktion ähnlich reguliert wird, wie aus in vitro-Versuchen bekannt ist. Deshalb wurde dieApoptose in verschiedenen Tiermodellen kardialer Erkrankungen untersucht werden, um Hinweise auf die zugrundeliegende Signal-transduktion, durch Analyseder Proteine Bcl-2 und Bax, der finalen Exekutor-Caspase Caspase-3 oder p53 zu bekommen. Apoptose in der durch Hyperlipidämie induzierten Atherosklerose: In Aorten von 'Froxfield Heritable Hypercholesterolemic'-Kaninchen (genetischeHyperlipidämie) korrelierte die Apoptose von vaskulären glatten Muskelzellen und Makrophagen in fortgeschrittenen fibrösen Plaques mit einem 18-fachenAnstieg des proapoptotischen Bax. In Aorten Cholesterin gefütterter 'New Zealand White'-Kaninchen (0,25% Cholest., 12 Wochen) konnte eine erhöhteBaxexpression in Endothelzellen nachgewiesen werden, ohne daß morphologische Veränderungen zu beobachten waren. Die Apoptose in akutabgestoßenen allogenen Herztransplantaten (Rattenmodell) war von einer erhöhten Bax-Expression und einer totalen, posttranslationalen Degradation desantiapoptotischen Bcl-2 in ein spezifisches Degradationsprodukt durch eine Serinprotease gekennzeichnet. Die Rolle des wichtigen kardiovaskulären Mediators Stickstoffmonoxid (NO) auf die Apoptose wird kontrovers diskutiert. Da in der Zellkultur protektiveEffekte von NO gezeigt werden konnten, wurde deren physiologische Relevanz in der durch Ischämie/Reperfusion induzierten Apoptose ex vivo imLangendorff-Rattenherzen untersucht. Es konnte gezeigt werden, daß Hemmung der endogenen NO-Synthese mit L-NG-Monomethyl-L-Arginin (LNMMA,1mM) die Apoptose potenzierte und mit einer Aktivierung der Caspase-3 korrelierte. Bcl-2 und Bax wurden nicht reguliert. Untersuchung der Regulation derProteinexpression der eNOS (endotheliale NO-Synthase) durch den proinflammatorischen/ proatherogenen Tumor-Nekrose-Faktor-[Alpha] (TNF[Alpha])in der Endothelzellkultur (HUVEC) gaben Hinweise auf einen, die eNOS schützenden, Interaktionspartner. Zusammenfassend konnte in allen untersuchten Modellen für Herz(-Kreislauf)-Krankheiten Apoptose nachgewiesen werden, die jeweils spezifischeCharakteristika zeigt, deren genauere Aufklärung interessante Ziele zukünftiger präventiver und therapeutischer Maßnahmen verspricht. Die Befunde weisenzudem auf antiapoptotische Effekte von NO - insbesondere durch die endotheliale NO-Synthaseaktivität - hin, deren genauere Charakterisierung dazubeitragen könnte, pathophysiologische Zustände der kardiovaskulären Biologie zu erklären.

Apoptosis is a distinct form of cell death that has been under intensive investigations in the past few years. Many signalling pathways were elucidated in cell-freesystems or in intact cells. But only little is known about apoptosis in cardiac and cardiovascular diseases. Therefore, the aim of this study was to investigateapoptosis in various cardiac diseases: in hyperlipidemia induced atherosclerosis, in acute rejected heart transplants, in ischemia and reperfusion as well as inchronic hypoxia. Atherosclerosis is the main contributor to myocardial infarction. Also hyperlipidemia is a known major risk factor. To investigate apoptosis in hyperlipidemia induced atherosclerosis, genetically induced hyperlipidemia in Froxfield Heritable Hypercholesterolemic Rabbits(FFH, n=8) was compared with New Zealand White rabbits either fed with a cholesterol diet (H, n=8, 0,25% cholesterol, 3% coconut oil) or with a normaldiet (control, n=5) for 12 weeks. To determine apoptosis DNA-laddering and immunohistochemical TUNEL-stainings were performed. In advanced fibrousplaques of FFH rabbits apoptosis of vascular smooth muscle cells (VSMCs) and macrophages (M|os) correlated with a drastic 18-fold increased expressionof proapoptotic Bax. The antiapoptotic protein Bcl-2 remained unchanged. In conclusion, apoptosis in advanced plaques seems to be a double edged sword:apoptosis of VSMCs may lead to plaque rupture due to diminished collagen synthesis and following myocardial infarction. In contrast, apoptosis of M|o couldinduce plaque stabilisation. Cholesterol diet did not induce morphological changes of the aortas in spite of elevated serum cholesterol. A doubling of Bax expression was observed inendothelial cells, indicating the induction of apoptosis in this cell type. Apoptosis of endothelial cells could be an initial manifestation leading to endothelialdysfunction and subsequent plaque development. The increased expression of Bax seems to correlate with elevated Low Density Lipoprotein (LDL) levels inboth models underlining the induction of apoptosis by elevated serum LDL. Heart transplantation is a common therapeutical option in the terminal stages of heart failure. The most important complications are acute rejection and chronicvasculopathy of the transplants. To investigate apoptosis as an effector mechanism of acute rejection, the model of allogenic heart transplantation from Wistar Furth to Lewis rats (n = 15)was used. These hearts were rejected from 6 to 10 days after transplantation. Apoptosis in acute rejected heart transplants was characterised by an enhanced(3-fold) expression of Bax. Bcl-2 was completely degraded into a specific degradation product of about 17 kD. An RNase protection assay with multipleprobes revealed no transcriptional changes of mRNA levels in acute rejected compared to control hearts. The posttranscriptional degradation of Bcl-2 wasfurther analysed in a radioactive assay in vitro. The involvement of a serine protease which is sensitive to nitric oxide (NO) and dithiotreitol (DTT) waseludicated. Apoptosis and in particular the elevated ratio of proapoptotic Bax to antiapoptotic Bcl-2 could be responsible for transplant rejection. In addition,the degradation of Bcl-2 could also contribute to transplant rejection probably due to diminished antiapoptotic Bcl-2 levels or by producing an apoptoticdegradation fragment. Myocardial infarction is either a consequence of atherosclerotic vessel occlusion or of transplantation. Typically it is accompanied by a loss of cardiomyocytes.Ischemia/ reperfusion is an accepted model for myocardial infarction. To investigate apoptosis in ischemia/reperfusion, hearts from male Wistar Furth rats were perfused ex vivo in a Langendorff apparatus (n=6 per group; 30minutes equilibration, 30 min. global ischemia, 30 min. reperfusion). Reperfusion, but not ischemia alone induced apoptosis. Apoptosis was accompanied bythe activation of caspase-3, a member of the apoptosis inducing caspase-cascade (as determined by western blotting and a radioactive assay in vitro). In contrast to acute hypoxia in ischemia, chronic hypoxia in Wistar Furth rats (21 days 10% O2, n=4) resulted in apoptosis of the hearts which wascharacterised by a doubling of proapoptotic Bax and a halffold reduction of antiapoptotic Bcl-2. Thus the enhanced ratio of Bax to Bcl-2 could be responsiblefor apoptosis in chronic hypoxia. Myocardial diseases are often accompanied by a reduction of endogenous nitric oxide. The role of nitric oxide in apoptosis is discussed controversially. The physiological relevance of antiapoptotic NO-effects was demonstrated in ischemia/ reperfusion experiments. Inhibiting the endogenous NO-synthase inischemia/reperfusion with its competitive inhibitor L-NG-Monomethyl-L-arginine (LNMMA, 1 mM) potentiated apoptosis. In addition, caspase-3 wasactivated suggesting protective effects of the endogenous NO production due to an inhibiting interference with caspase-3. These results were underlined by the observations that hearts of endothelial nitric oxide synthase (eNOS)-knockout-mice (n=2 per group) showedapoptosis, which correlated with an elevated Bax expression. All taken together, apoptosis was demonstrated in all models under investigation. Apoptosis shows specific characteristic features in the distinctcardiac/cardiovascular diseases providing future targets for prevention and therapy. Proatherosclerotic and proinflammatoric factors are known to inhibit endogenous NO release. Therefore, the regulation of eNOS protein synthesis in responseto tumour necrosis factor [Alpha] (TNF[Alpha]) in the presence of cycloheximide (CHX, an inhibitor of protein synthesis) was analysed in human umbilical veinendothelial cell cultures (HUVEC). The apoptotic stimuli TNF[Alpha]/CHX resulted in the proteolysis of eNOS. The diminished eNOS protein levels wereaccompanied by a reduced enzyme activity suggesting an antiapoptotic function of the endogenous NO synthesis. Inhibition of the proteasome with ZLLLH, aproteasome-specific inhibitor, only reversed eNOS proteolysis induced by TNF[Alpha]/CHX indicating the involvement of a protein which is interacting witheNOS. eNOS itself seems not to be degraded by the proteasome, because ZLLLH had no effect on TNF[Alpha] induced degradation. In conclusion, theseresults suggest the presence of a protective eNOS associated protein which is degraded by TNF/CHX leading to a subsequent degradation of eNOS. Thechaperone Hsp90 could be such an eNOS interacting protein. However, in our system we could not observe a significant role of HSP70 or Caveolin-1 ineNOS degradation. Immunoprecipitation studies revealed the involvement of an eNOS interacting protein of around 70 kD molecular weight. This protein hasstill to be identified. In summary, nitric oxide, especially derived from eNOS, seems to be protective against apoptotic cell death. Elucidating the mechanisms leading to adecreased NO production by the eNOS could help to explain pathological disorders of the cardiovascular biology.
Keywords: ddc:570